2018
DOI: 10.1182/blood-2018-05-844928
|View full text |Cite
|
Sign up to set email alerts
|

Macrophage TNF-α licenses donor T cells in murine bone marrow failure and can be implicated in human aplastic anemia

Abstract: Abstract Interferon-γ (IFN-γ) and tumor necrosis factor-α (TNF-α) have been implicated historically in the immune pathophysiology of aplastic anemia (AA) and other bone marrow (BM) failure syndromes. We recently defined the essential roles of IFN-γ produced by donor T cells and the IFN-γ receptor in the host in murine immune-mediated BM failure models. TNF-α has been assumed to function similarly to IFN-γ. We used our murine models and mice genetically deficient … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
54
3

Year Published

2019
2019
2023
2023

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 54 publications
(59 citation statements)
references
References 58 publications
(73 reference statements)
2
54
3
Order By: Relevance
“…However, our data indicate that the number of Tregs in the bone marrow of AA patients is not predictive for the response to ATG therapy. Regarding MΦs, and in contrast to the study by Sun et al 44 , we found that AA patients had fewer MΦs, both of the CD68 and CD163 subtypes, than healthy controls. In an AA mouse model, MΦs produced TNF-α and through the TNF-α receptor engaged effector T cells and increased the production of IFN-γ 44 .…”
Section: Discussioncontrasting
confidence: 99%
See 1 more Smart Citation
“…However, our data indicate that the number of Tregs in the bone marrow of AA patients is not predictive for the response to ATG therapy. Regarding MΦs, and in contrast to the study by Sun et al 44 , we found that AA patients had fewer MΦs, both of the CD68 and CD163 subtypes, than healthy controls. In an AA mouse model, MΦs produced TNF-α and through the TNF-α receptor engaged effector T cells and increased the production of IFN-γ 44 .…”
Section: Discussioncontrasting
confidence: 99%
“…Recently, it was shown that macrophages (MΦs) play a central role in IFN-γ-related stem cell destruction. Specifically, they produce tumor necrosis factor-a (TNF-a), engage cytotoxic T cells, and consequently enhance the production of IFN-γ, forming an interactive loop [44][45][46] . Another important aspect involves regulatory T cells (Tregs), which are decreased in AA.…”
Section: Immunological Mechanismsmentioning
confidence: 99%
“…It is a negative regulator of hematopoiesis. Neal S Young et al demonstrated that TNF-α -/aplastic anemia mice were resistant to bone marrow destruction induced by allogeneic LN cell infusion and suggested that TNF-α was closely associated with apoptosis in AA [55]. In addition, studies have demonstrated that IFN-γ induces TNF-α production in mouse macrophages through IFN regulatory factors, IFN-1 and IFN-8.…”
Section: T Lymphocytes and Their Secreted Cytokinesmentioning
confidence: 99%
“…This hypothesis coincides with recent studies in murine models of acute AA showing that TNFα, which is generated by host macrophages in response to infused T cells, accelerates immune-mediated BM destruction. 53 Reduced IL-2 expression observed in mice that receive DGKζ-deficient cells is consistent with rapid onset of activation, leading to functional decline of antigen-specific effector T cells that could result in their depletion. Exhaustion of rapidly expanding effector T cell populations is said to explain stronger antitumor effects in xenotransplanted DGKζ -/mice.…”
Section: Discussionmentioning
confidence: 82%